Karakteristik Klinis dan Patologis Pasien Tumor Parotis di RSUP Dr. M. Djamil Padang - Astri Sentyaningrum; Sukri Rahman; Roslaili Rasyid (Fakultas Kedokteran, Universitas Andalas, 2021)
Background: Parotid tumor is a tumor supporter of saliva that occurs most often among the tumors present in other saliva. Parotid tumor is a tumor with a slow progression rate, so that it makes patients serve to seek treatment.Objective: This study aims to determine the characteristics of parotid tumor patients in RSUP. Dr. M. Djamil Padang.Methods: This type of research is descriptive with a retrospective approach. This research was conducted from March to August 2020 at the Medical Record Installation of Dr. M. Djamil Padang with a total sample of 30 people and used a total sampling technique.Results: The most cases of parotid tumor were found in 2018. Parotid tumors were more often seen in women than men with the largest age range of 51 - 60 years. The main complaint is generally a lump behind the ear. Parotid tumor clinical symptoms consist of a lump behind the ear, followed by pain in the lump and others. The most histopathological types found were pleomorphic adenoma for the benign type and mucoepidermoid carcinoma for the malignant type.Conclusion: parotid tumors are more common in women, the most age range is 51 - 60 years, the main complaint is generally a lump behind the ear. The most clinical symptoms are a lump behind the ear, and the most benign parotid tumor histopathology is pleomorphic adenoma while the malignant type is carcinoma. mucoepidermoid.